Capacity Building in Millennials Posyandu of Pangkajene and Island Regency - Fatttah, Indrayati; Lambali, Suryadi; Yunus, Muhammad (LEGAL BRIEF, 2023)
This journal article explores the concept of capacity building within the context of the Millennial Integrated Service Post (Posyandu) program in Pangkajene and Island Regency. The study delves into the strategic approach of capacity building, focusing on establishing and developing a program that addresses the health needs of the millennial generation. Through partnership-based initiatives, community activation, collaboration, information sharing, network density, and service reorientation are examined as key indicators of capacity enhancement. The research highlights the program's successes and challenges, showcasing how collaborative efforts, adaptive service delivery, and innovative strategies contribute to effective capacity building. Insights from this study offer valuable guidance for improving youth health services through a comprehensive and participatory approach.